2010
DOI: 10.1021/jp1099514
|View full text |Cite
|
Sign up to set email alerts
|

Quest for Spatially Correlated Fluctuations in the FMO Light-Harvesting Complex

Abstract: The light absorption in light-harvesting complexes is performed by molecules such as chlorophyll, carotenoid, or bilin. Recent experimental findings in some of these complexes suggest the existence of long-lived coherences between the individual pigments at low temperatures. In this context the question arises if the bath-induced fluctuations at different chromophores are spatially correlated or not. Here we investigate this question for the Fenna-Matthews-Olson (FMO) complex of Chlorobaculum tepidum by a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
222
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(234 citation statements)
references
References 70 publications
(189 reference statements)
8
222
4
Order By: Relevance
“…In contrast, the measured spectral linewidths predict electronic dephasing times at 77 K hardly exceeding 100 fs [11], owing to rapid, stochastic variations in the environment, and coherences between excitons are expected to decay roughly on this timescale. The long coherence times could be explained by correlations between the fluctuating electronic site transition energies, but these are not concordant with recent molecular dynamics simulations [12,13].…”
Section: Introductioncontrasting
confidence: 73%
“…In contrast, the measured spectral linewidths predict electronic dephasing times at 77 K hardly exceeding 100 fs [11], owing to rapid, stochastic variations in the environment, and coherences between excitons are expected to decay roughly on this timescale. The long coherence times could be explained by correlations between the fluctuating electronic site transition energies, but these are not concordant with recent molecular dynamics simulations [12,13].…”
Section: Introductioncontrasting
confidence: 73%
“…Recent molecular dynamics (MD) simulation studies on the Fenna-Mathews-Olsen (FMO) excitation energy transfer network, 11,12 the light harvesting complex 2 (LHII) photosynthetic light harvesting complex 13 and the reaction center complex, 14 however, show no significant correlation in site energy fluctuations after averaging, and similar findings have been reported from calculations for the PE545 15 light harvesting system. However, Kleinekathöfer and co-workers, for example, have found that in FMO, 11 there is evidence of correlations in fluctuations of site energy and inter site electronic couplings and electronic coupling-electronic coupling correlations that are more significant compared to the apparently uncorrelated site energy fluctuations.…”
Section: Introductionmentioning
confidence: 58%
“…Several theoretical groups [11][12][13][14][15] have begun exploring detailed microscopic simulation models looking for different types of environment driven correlated fluctuations in chromophore electronic properties. The ubiquitous finding from the various photosynthetic energy transfer systems studied so far is that fluctuations in site energies seem to be such that on average they are uncorrelated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations